PENGARUH KEKURANG-TEPATAN DATA MASUKAN DALAM PERENCANAAN PERKERASAN JALAN LENTUR - Nono Nono (Jurnal Jalan-Jembatan, 2006)
In general, the pavement design methods in Indonesia are adopted from pavement design methods of AASHTO or TRL, such as flexible pavement design with analysis component methods (structural number analysis). The effectiveness of design result depend upon the use of design input, completeness and accuracy of data, that is traffic data, environmental or regional factor and terminal serviceability index (Pt). This paper discusses the effect of incaccurately inputing data, which is used for the design result.Design result showed that uncorrect determination decided of regional factor, terminal serviceability index (Pt) and the use of the equivalent standart axles of Austroad formula have a significant impact on it.